Distinctive metabolite profiles in migrating Amur ide (Leuciscus waleckii) reveal changes in osmotic pressure, gonadal development, and energy allocation strategies - Wang, Shuangyi; Huang, Jing; Liang, Liqun; Su, Baofeng; Zhang, Yu; Liew, Hon Jung; Sun, Bo; Zhang, Limin; Chang, Yumei (Frontiers in Environmental Science, 2022)
Amur ide (Leuciscus waleckii) lives in alkali-saline water (pH = 9.6) in the Lake Dali and spawns in freshwater rivers after migration annually. During spawning migrations, Amur ide not only experience osmoregulation modification from alkali-saline water to freshwater but also deal with energy prioritization for basal metabolism and gonadal development. To achieve an optimal cost-benefit balance, a series of metabolism modifications are needed. This study investigated the changing metabolite profiles that contribute to maintaining a balance of osmotic pressure and energy allocation for gonadal maturation. We applied ultra-performance liquid chromatography together with quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS), combined with chemometrics, for identifying metabolic changes regarding spawning broodstocks of Amur ide during migration. According to findings, there were 11,333 metabolites in Amur ide serum and 3,159 metabolites were found to change significantly during migration. Differentially expressed metabolites mainly affected the steroid hormone biosynthesis, the arachidonic acid metabolism, the biosynthesis of phenylalanine, tyrosine, and tryptophan, pyruvate metabolism, citrate cycle, as well as glycerophospholipid metabolism. Based on the enrichment analysis regarding metabolic pathways, biosynthesis of steroid hormone and arachidonic acid metabolism are two representative pathways, which are crucial for osmoregulation and gonadal maturation. The perturbation of some metabolites during migration was highlighted, which involves sexual maturation and reproduction, nitrogenous waste excretion, and energy allocation. The study assists in understanding the physiological plasticity exhibited by Amur ide during migratory spawning from a new perspective, which is useful as a scientific basis for the artificial breeding of Amur ide and other anadromous fish.